The Role of Marketing Capability, Operations Capability, Management Practices and Environmental Investment on Agro-Industrial Environmental Performance - Awatara, I Gusti Putu Diva; Hamdani, Anwar; Susila, Linda Nur; Saryanti, Endang (AIBPM Publisher, 2020)
This study aims to investigate the role of marketing capability, operations capability, management practices and environmental investment on the environmental performance of agro-industry companies. This research conducted a survey research on all employees of 120 agroindustry companies. The samples were selected with proportionate stratified random sampling based on management level of the companies. The data were compiled from questionnaires and field observations. After the validity and reliability test, a set of classical assumptions were undergone to determine the variable relations, along with the hypothesis testing with multiple linear regression, t test and F test. The results of this study indicate that marketing capability, operations capability, management practices, and environmental investments have effects on environmental performance.